STUDI IMBANGAN AIR PADA DAERAH IRIGASI PITAP - Fitriati, Ulfa; Novitasari, Novitasari; Rusdiansyah, Achmad; Rahman, Andi (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2015)
To fulfilling the demands of irrigation water in the region SWS Barito mostly farming community life is indispensable. Due to the presence of water balance studies in Sub SWS Barito is the basis for preparing the development strategy of water resources, particularly water management in irrigation area as one sub DAS Pitap Barito River. The method used to perform the analysis of the availability of water by using methods Mock and irrigation water needs analysis to see the balance of water in the water supply for paddy in Pitap Irrigation Area. Balance of water in the dam Pitap still insufficient to meet the water demands Pitap irrigation area of 4000 ha.Key Words: water availability, water demand, water balance and irrigation area Pitap